Governance Trilemma On The “Green-Blue Economy” Integration In Global Environmental Policy Making - Bambang Wahyu Nugroho; Grace Lestariana Wonoadi (Universitas Jenderal Ahmad Yani, 2026)
This study examines the integration of land-based green and ocean-based blue economies, which remain separately governed despite shared relevance to the SDGs and Paris Agreement. Analyzing five national through a comparative case study method, it identifies four integration models, i.e (1) necessity-driven, (2) technocratically-driven, (3) opportunity-driven, and (4) fragmented. Those are shaped by local political-economic factors. A key finding is a governance trilemma, where mobilizing finance, controlling cross-boundary externalities, and ensuring procedural justice are rarely balanced. The article advances beyond normative calls for integration by specifying conditions for success or failure, and offers a diagnostic tool for policymakers. It concludes that effective green-blue integration demands context-sensitive architectures that jointly address finance, externalities, and justice as foundations for resilience and equity.